Sammlung Ackermans : anlässlich der Eröffnung des Museums Kurhaus Kleve - Ewald Mataré Sammlung. - Bieger-Thielemann, Marianne; Braun, Alexander; Britt-Koerner, Swantje; De Werd, Guido; Dziewior, Yilmaz; Geisselbrecht-Capecki, Ursula; Heinrich, Christoph; Hucht, Margarete; Janus, Elisabeth; Kersting, Rita; Kopp, Ursula; Kratz, Paul; et al. (Köln : Salon Verlag, 1997)
Merz, Mario ; Pistoletto, Michelangelo ; Penone, Giuseppe ; Kounellis, Jannis ; Boltanski, Christian ; Kiefer, Anselm ; Herold, Georg ; Kippenberger, Martin ; Oehlen, Albert ; Polke, Sigmar ; Metzel, Olaf ; Fritsch, Katharina ; Honert, Martin ; Hablützel, Stefan ; Stadtbäumer, Pia ; Kütz, Walter ; Ruff, Thomas ; Mundt, Wilhelm ; Virnich, Thomas ; Pitz, Hermann ; Schütte, Thomas ; Balkenhol, Stephan ; Mucha, Reinhard ; Brandl, Herbert ; West, Franz ; Fischli & Weiss ; Muñoz, Juan ; Gilbert & George ; Art & Language ; Linke, Simon ; Cragg, Tony (Anthony) ; Deacon, Richard ; Woodrow, Bill ; Gober, Robert ; Oursler, Tony ; Chamberlain, John ; Oldenburg, Claes ; Rollins, Tim & K.O.S. ; Schnabel, Julian ; Salle, David ; Sherman, Cindy ; Wall, Jeff ; Warhol, Andy
biografie, bibliografie
Duits
boek